Perspectives of individuals with multiple sclerosis on discontinuation of disease-modifying therapies. (October 2020) - McGinley, Marisa P; Cola, Philip A; Fox, Robert J; Cohen, Jeffrey A; Corboy, John J; Miller, Deborah
Background: Therapeutic research in multiple sclerosis (MS) has focused on the development of treatments with little investigation regarding the possibility of discontinuation of disease-modifying therapies (DMTs). Objective: To understand the opinion of individuals with MS concerning stopping DMTs and the factors that influence the decision-making process. Methods: A mixed method approach was used starting with three focus groups from which a survey was developed. This survey was sent to 1000 participants in the North American Research Committee on Multiple Sclerosis registry who met inclusion criteria (age ⩾45 years; on most recent DMT for ⩾5 years). Descriptive analysis and structural equation modeling were used. Results: Of 1000 participants receiving the survey, 377 provided complete responses and met inclusion criteria. Only 11.9% of participants reported that if their disease was considered stable, they would consider coming off medications. A high level of external locus of control in influential others such as physicians significantly decreased the likelihood of considering discontinuation. Conclusions: Most individuals with MS report being unlikely to consider stopping MS therapy if their disease was considered "non-active." As the results of studies concerning DMT discontinuation are obtained, information from providers will be an important part of individuals' decision-making process.